2019
DOI: 10.1093/ajcn/nqz195
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and the risk of congenital anomalies in subsequent pregnancies

Abstract: Background Data on the relationship between bariatric surgery and risk of birth defects are conflicting. Objectives We studied the association of bariatric surgery with birth defects in future pregnancies in a large cohort of women. Methods We carried out a retrospective cohort study of 2,194,348 pregnancies that occurred between 1989 and 2016 in Quebec, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…After exact matching, Neovius et al (2019) found a decreased relative risk for major congenital defects (RR 0.67, 95% CI 0.52–0.87, P = 0.002). The other articles found no significant association between bariatric surgery and the incidence of congenital malformations ( Sheiner et al , 2004 , 2006 ; Josefsson et al , 2013 ; Parent et al , 2017 ; Auger et al , 2019 ).…”
Section: Resultsmentioning
confidence: 89%
“…After exact matching, Neovius et al (2019) found a decreased relative risk for major congenital defects (RR 0.67, 95% CI 0.52–0.87, P = 0.002). The other articles found no significant association between bariatric surgery and the incidence of congenital malformations ( Sheiner et al , 2004 , 2006 ; Josefsson et al , 2013 ; Parent et al , 2017 ; Auger et al , 2019 ).…”
Section: Resultsmentioning
confidence: 89%
“…We classified heart defects as critical (tetralogy of Fallot, coarctation of the aorta, transposition of great vessels, truncus arteriosus, hypoplastic left heart, common ventricle, other) or noncritical (atrial septal defect, ventricular septal defect, endocardial cushion defect, pulmonary artery defects, heterotaxy, other). 25 Critical defects require urgent intervention at birth and may cause severe sequalae or death if not treated promptly. 26 …”
Section: Methodsmentioning
confidence: 99%
“…FA supplementation helps to reduce circulating Hcy levels in patients taking antiepileptic drugs [ 68 ]. It is also used regularly to combat folate deficiency anemia resulting from the excessive intake of alcoholic beverages, post-bariatric surgery [ 69 ], and in conjunction with methotrexate in rheumatoid arthritis [ 70 ].…”
Section: Folate Malabsorptionmentioning
confidence: 99%